Amorphous boron composite gaskets for in situ high-pressure and high-temperature studies. Issue 4 (1st October 2016) - Rosa, A. D.; Merkulova, M.; Garbarino, G.; Svitlyk, V.; Jacobs, J.; Sahle, Ch.J.; Mathon, O.; Munoz, M.; Merkel, S.
ABSTRACT: The diamond anvil cell (DAC) is a fundamental device used to explore the properties of materials under extreme pressure and temperature ( P/T ) conditions. In the past years, simultaneous high P/T DAC experiments using the resistively heated DAC (RH-DAC) techniques have been developed for studying materials properties in a wide P/T range. However, the mechanical instability of metallic gaskets used for sample confinement at high P/T conditions remains a limiting factor for exploiting the accessible P/T range of the RH-DAC. In this study, we present a new gasket configuration that overcomes these limitations. It is based on an amorphous boron–epoxy mixture inserted in a rhenium gasket. We show how these gasket inserts stabilize the sample chamber over a wide P/T range, allowing monitoring sample properties using X-ray diffraction and absorption spectroscopy up to 50 GPa and 1620 K.